2021
DOI: 10.1111/ijn.12913
|View full text |Cite
|
Sign up to set email alerts
|

Heparin versus 0.9% saline solution to maintain patency of totally implanted venous access ports in cancer patients: A systematic review and meta‐analysis

Abstract: Aim The use of heparin and 0.9% saline solution is always controversial for central venous catheters. However, there is no systematic review or guideline about whether saline solution can replace heparin solution in adult cancer patients with totally implantable venous access ports (TIVAPs). The purpose of this review is to evaluate whether saline solution can replace heparin saline to lock TIVAPs. Methods The following databases were searched: PubMed, the Cochrane Library, Web of Science, Embase, CINAHL and O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…6,26 Fourth, we chose to use heparinized 0.9% NaCl solution before insertion, but used 0.9% NaCl after each treatment and every month thereafter. In 2021, Wu et al 27 suggested that there was no difference between 1/10 heparinized and non-heparinized NaCl solutions. Guidelines for TIVAD recently prefer non-heparinized NaCl solution.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…6,26 Fourth, we chose to use heparinized 0.9% NaCl solution before insertion, but used 0.9% NaCl after each treatment and every month thereafter. In 2021, Wu et al 27 suggested that there was no difference between 1/10 heparinized and non-heparinized NaCl solutions. Guidelines for TIVAD recently prefer non-heparinized NaCl solution.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Its advantage is that the use is not limited by the type of disease. It is especially suitable for patients with bleeding tendency, disturbance of blood coagulation mechanism and insufficiency of liver and kidney [ 11 ]. Heparin sodium is a highly effective anticoagulant, it has been reported that heparin sodium can reduce venous thrombosis and maintain vascular patency [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] In fact, heparin use as a catheter lock solution is a risk factor for biofilm formation and infections. [23][24][25] Access to ELT has also been inconsistent because of changes in price and availability, leaving high-risk patients with no antimicrobial alternative. 26 European guidelines recommend the use of taurolidine locks for secondary prevention of CLABSI.…”
Section: Introductionmentioning
confidence: 99%
“…Heparin is less effective for infection prophylaxis in patients with intestinal failure and ELT increases the rate of mechanical complications 20–22 . In fact, heparin use as a catheter lock solution is a risk factor for biofilm formation and infections 23–25 . Access to ELT has also been inconsistent because of changes in price and availability, leaving high‐risk patients with no antimicrobial alternative 26 .…”
Section: Introductionmentioning
confidence: 99%